2021
DOI: 10.7717/peerj.10739
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes influencing anthocyanin biosynthesis during the development and ripening of red and white strawberry fruits via comparative transcriptome analysis

Abstract: Strawberries are one of the most economically important berry fruits worldwide and exhibit colours ranging from white to dark red, providing a rich genetic resource for strawberry quality improvement. In the present study, we conducted transcriptome analyses of three strawberry cultivars, namely, ‘Benihoppe’, ‘Xiaobai’, and ‘Snow White’, and compared their gene expression profiles. Among the high-quality sequences, 5,049 and 53,200 differentially expressed genes (DEGs) were obtained when comparing the diploid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
(104 reference statements)
1
10
1
Order By: Relevance
“…These results suggested that the FaMYB10 gene may not be directly responsible for the loss of anthocyanins in Xiaobai's flesh. Herein, we demonstrated that the inhibition of the C4H gene was the main factor responsible for the absence of anthocyanins in Xiaobai, which differed from previous reports [14,23,30]. C4H not only affects the flavonoid biosynthesis but is also necessary for the biosynthesis of osthole, hydroxycinnamic acids, dihydrochalcones, eugenol, lignin, and ubiquinone [4][5][6][7].…”
Section: Discussioncontrasting
confidence: 76%
“…These results suggested that the FaMYB10 gene may not be directly responsible for the loss of anthocyanins in Xiaobai's flesh. Herein, we demonstrated that the inhibition of the C4H gene was the main factor responsible for the absence of anthocyanins in Xiaobai, which differed from previous reports [14,23,30]. C4H not only affects the flavonoid biosynthesis but is also necessary for the biosynthesis of osthole, hydroxycinnamic acids, dihydrochalcones, eugenol, lignin, and ubiquinone [4][5][6][7].…”
Section: Discussioncontrasting
confidence: 76%
“…RNAseq has been used to unravel intricate processes at the molecular level, such as fruit development and ripening in commercial strawberries (Sanchez-Sevilla et al, 2017 ; Gu et al, 2019 ; Zhao et al, 2021 ). The description of a massive number of genes in the Chilean strawberry is described for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…They are synthesized at the endoplasmic reticulum and later transported into the vacuole for storage mainly by glutathione S-transferases (GSTs) ( Luo et al., 2018 ; Castillejo et al., 2020 ). Among the anthocyanins, pelargonidin-3-glucoside is the major pigment in strawberry receptacles, while cyanidin-3-glucoside is present in a minor content ( Almeida et al., 2007 ; Zhao et al., 2021 ). Finally, for the biosynthesis of PAs, two main enzymes are involved, i.e., leucocyanidin reductase (LAR) and anthocyanidin reductase (ANR).…”
Section: Regulation Of the Phenylpropanoid Pathwaymentioning
confidence: 99%